Rekonstruksi Sistem Informasi Akuntansi Pada PT. NURTIWI - Beni Nurochman; Nining Ika Wahyuni; Alwan Sri Kustono (UPT Penerbitan Universitas Jember, 2019)
PT NURTIWI is a manufacturing company engaged in the field of furniture that is growing using the accounting information system based Zahir Accounting application, to facilitate the company in decision making. So the author's goal is to analyze and design the information system by making supporting data in the process of input data into accounting information system based Zahir application in the form of Microsoft Excel in order to facilitate the director or employees of the company in making decisions to determine company policy to be taken. In his research the authors used a qualitative approach with descriptive research design, focusing on the systematic explanation of the facts obtained when the research was conducted. The result of SIA analysis applied by PT NURTIWI still has weakness especially in purchasing and supply part, delay in recording of supplier's debt card, and repayment of trade payable, stock card, general journal no grouping of production cost between raw material cost, factory overhead cost and direct labor cost insert per item code. The lack of manpower within the company raises the Administration and Finance in the company’s administrative process to experience delays. Keywords: Decision Making, Reconstruction, Accounting Information Systems, Zahir Accounting